Historicité du sexe - Dorlin, Elsa (Sexe, genre et sexualités : introduction à la théorie féministe, 2008)
Keywords: 1900-1999; afro-féminisme; approches et analyses; biopolitique; cours; discipline; essentialisation; féminisme décolonial; féminismes noirs; genre; his4330; naturalisation; phi4336; philosophie politique; premier cycle; production des savoirs; périodes historiques; queer; rapports sociaux de sexe; ressource en ligne; sciences humaines; sex3383; sexe/genre; sexualité; thématiques; théorie féministe; épistémologies féministes

Femme nue, femme noire: roman - Beyala, Calixthe (Librairie générale française, 2005)
Belle, attirante, indomptable, Irène n'a, de son propre aveu, que deux passions : voler et faire l'amour. C'est ainsi qu'elle s'empare un jour d'un sac à main et quelle y découvre... un bébé mort. Peu après, elle rencontre Ousmane, un nouvel amant qui l'entraîne dans une spirale de débauche et de provocation... Mais dans une Afrique noire urbaine où la misère et l'immobilisme vont de pair avec la résignation, y a-t-il place pour la révolte qu'elle tente ainsi de faire entendre ? C'est une fable mélancolique que nous conte ici Calixthe Beyala, sous les apparences d'un roman érotique à la sensualité débridée et à l'humour corrosif.
Section: 188 p. : couv. ill. ; 18 cm.
Keywords: afrique; afro-féminisme; approches et analyses; arts; cours; discipline; féminisme africain; féminismes noirs; lit4700; littérature; littérature érotique; premier cycle; roman; régions géographiques; sexualité; thématiques; écriture des femmes*; études littéraires

Black sexual politics: African Americans, gender, and the new racism - Hill Collins, Patricia (Routledge, 2005)
To a large extent, scholarship on black politics often focuses primarily on institutions, rule of law, processes, political actors, and citizens but with very little attention to issues of gender and sexuality. In contrast, the principal aim of this book is to explore what the author sees as the inextricable links between racism and gender. The basic thesis of this well-written, important, and provocative book is that the fight against racism, especially the “new racism,” can never be won without first challenging sexism, which simultaneously oppresses African-American men and women.
Section: ix, 374 p. ; 23 cm
Keywords: afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; féminismes noirs; intersectionnalité; premier cycle; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; théorie critique de la race; violences; états-unis

The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis